Effectiveness of an Interventional Program on Nurses’ Practices Toward Patients’ Safety Post Coronary Angiography - Khulood A. Maktoof; Rajaa I. Abed (مجلة كلية الطب)
Background: Nurses have a critical role for maintaining patients safe during coronary angiography procedures. In the coronary care unit, patient's safety is critical in reducing complications. Everyone is entitled to high-quality healthcare that is both safe and efficient. Objectives: to evaluate the effect of a patient’s safety intervention program on the nursing staff after coronary angiography. Methods: A quasi-experimental study carried out in the cardiac medical ward and cardiac care unit (CCU) at Al-Nasiriyah Heart Center from 4th of June to 27th of November 2023. The program and tools for the study were made by the researcher. A purposive (non-probability) sample of fifty nurses who were divided (into two groups in order to achieve the objectives of the research: the study group, which consisted of twenty-five nurses who had taken part in the nursing training program, and the control group, which also consisted of twenty-five nurses. The data collection instrument consisted of two primary sections; in the first section, a designated sheet with six items was used to determine the demographic characteristics of these nurses. In the second section, an observational tool checklist) with eighteen items was used to determine the nurses' practices regarding patient safety after coronary. An descriptive and inferential statistical data analysis were applied by using the statistical package for social sciences(SPSS) version 26.The interventional program has been designed to provide the nurse with standard practice concerning the safety of patients post  coronary angiography in three sessions and application of nursing care with sample group on patients in cardiac care. Results: The study's findings demonstrated the beneficial effects of the nursing interventional program on nurses' post-coronary angiography patient safety practices at P-value =0.001. It was discovered during posttest procedures. Conclusion: This outcome demonstrates that nurses' post-coronary angiography patient's safety procedures were positively impacted by the interventional program.